Academic competitiveness and prosocialness of university students - Daliva, Mary Diane D.
This study focused on examining the academic competitiveness and prosocialness of university students, specifically 4th year students aged 21 to 25 from various degree programs at Capiz State University - Pontevedra Campus. Academic competitiveness refers to desire for academic excellence, surpassing peers, and achieving higher levels of academic success (Cretsinger, 2003). Prosocialness, on the other hand, encompasses attitudes such as empathy, kindness, sharing, and cooperation, which contribute to the well-being of individuals, others, and society (Eisenberg & Fabes, 1998). Using a quantitative research design, the study employed well-established scales with established psychometric properties: the Competitive Attitude Scale (CAS) and the Prosocialness Scale for Adults (PSA). The study was conducted both face-to-face and virtually. The data collected were analyzed using descriptive statistics, t-tests, analysis of variance (ANOVA), and correlation analysis. The results revealed several noteworthy findings. Firstly, the university students displayed a moderate level of academic competitiveness, indicating a drive for academic excellence without excessive competitiveness. Additionally, the participants exhibited a high level of prosocialness, showing a willingness to engage in actions that benefit other. The analysis also discovered a weak but significant relationship between academic competitiveness and prosocial behavior. This suggests that as academic competitiveness increases, there is a slight tendency for prosocial behavior to increase as well. Although the correlation between the two variables was not particularly strong, the significance of the relationship highlights a connection between academic competitiveness and prosocialness. Keywords: academic competitiveness, prosocialness, state university, Filipino.